Edge plasma properties with 3D magnetic perturbations in RFX-mod. (31st May 2017) - Agostini, M.; Scarin, P.; Spizzo, G.; Auriemma, F.; Cappello, S.; Carraro, L.; Marrelli, L.; Spagnolo, S.; Spolaore, M.; Veranda, M.; Vianello, N.; Zuin, M.
Abstract: The response of the edge plasma to a magnetic perturbation (MP) is studied in the RFX-mod device, in both reversed field pinch (RFP) and tokamak discharges. The use of spatially distributed diagnostics, in particular along the poloidal direction, allows a direct 3D characterization of the plasma. It is shown that there is a difference between the spectrum of the MP and that of different properties of the edge plasma, such as the floating potential, the electron pressure and the flow, for both RFP and tokamak plasmas. In particular, for RFP cases, even if the magnetic perturbation is mainly m   =  1, with the amplitude of the m   =  0 and m   =  2 sidebands negligible, the connection length to the wall of the magnetic field L cw has a more complex structure. The ergodic regions, with L cw larger than the Kolmogorov length, are due to the interaction of both m   =  1 and m   =  0 modes, showing a complex and non-monochromatic behaviour along the poloidal angle. This structure of L cw is responsible for the impure m   =  1 behaviour of the plasma wall interaction, floating potential and electron pressure. Thus the helicity of the edge plasma is quite different from that of the dominant MP.